2010
DOI: 10.1111/j.1651-2227.2010.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings associated with abnormal lung function in children aged 3–26 months with recurrent respiratory symptoms

Abstract: The results of this study emphasize the importance of the meticulous clinical examination in the evaluation of early childhood respiratory disorders. As physical examination alone cannot predict lung function abnormalities reliably in preschool children with troublesome respiratory symptoms, lung function testing may be considered in such patients to obtain additional objective information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Whole body plethysmography is not frequently used in infants due to its complexity and the necessity of highly trained staff. Nonetheless, it has been shown to be able to determine the severity of respiratory disorder in infancy (Kjaer et al 2008, Pelkonen et al 2010, Robin et al 2004 and to identify air trapping.…”
Section: Clinical Findings and Interpretationmentioning
confidence: 99%
“…Whole body plethysmography is not frequently used in infants due to its complexity and the necessity of highly trained staff. Nonetheless, it has been shown to be able to determine the severity of respiratory disorder in infancy (Kjaer et al 2008, Pelkonen et al 2010, Robin et al 2004 and to identify air trapping.…”
Section: Clinical Findings and Interpretationmentioning
confidence: 99%
“…In addition, reduced lung function was predictive for wheezy symptoms in the following years [61, [71][72][73]. Reduced lung function in infancy was associated with respiratory morbidity and treatment needs at preschool age [65]. Some studies showed improvement of lung function, such as forced expiratory volume in 0.5 s, in infants with recurrent wheezing after ICS treatment or oral treatment with montelukast, whereas others did not show significant changes [63,64,74,75].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…Different methods have been used to assess lung function in wheezy infants including the analysis of tidal flow-volume breathing loops, forced expirations from either normal inspiration (rapid thoracic compression technique) or from total lung capacity (raised volume rapid thoracic compression technique) or body plethysmography [62][63][64][65][66][67]. Infant lung function testing has been used to assess phenotypes in infants with wheezing and to develop prediction models for persistent asthma [68].…”
Section: Infant Lung Functionmentioning
confidence: 99%
“…In infants with wheeze, lung function may be assessed with several techniques, such as the analysis of tidal flow-volume breathing loops [114][115][116], forced expirations (rapid thoracic compression technique or raised volume rapid thoracic compression technique) [115,[117][118][119][120][121] or body plethysmography [122]. Infant lung function testing has been used to define phenotypes in infants with wheeze and to predict treatment effects and prognosis [120,121,[123][124][125]; several studies have tracked lung function from infancy to school age [115-117, 119, 126-131].…”
Section: Infant Lung Functionmentioning
confidence: 99%